Motivate Nurses with Compliance in Using Personal Protective Equipment (PPE) at The Jember Area Hospital - Putri, Prestasianita; Afandi, Alfid Tri; Veramawati, Tutut (Universitas Malahayati, 2024)
ABSTRACT During the current pandemic, nurses must use personal protective equipment properly. Nurses' compliance with the use of personal protective equipment needs self-motivation from nurses. This study aims to identify the motivation of nurses, identify compliance with the use of personal protective equipment, and analyze the relationship between motivation and compliance with the use of personal protective equipment. The independent variable in this study is motivation, while the dependent variable is nurse compliance. This study has 138 respondents using a sampling technique that is purposive sampling. The design of this study uses a type of correlation with a cross-sectional approach. Bivariate statistical test using Chi-Square. The results of this study are that the motivation of nurses is sufficient at 95.7%, compliance with the use of personal protective equipment is 90.6%, and there is no relationship between the motivation of nurses and the use of personal protective equipment at Hospital in Jember with p = 0.419 (p>0.05). From this study, it was found that there was no relationship between the motivation of nurses and the use of personal protective equipment at the Hospital in Jember. The role of hospitals in increasing compliance with the use of personal protective equipment by conduct training on the use of personal protective equipment and preparing personal protective equipment for nurses. Keyword: Personal Protective Equipment, Compliance, Motivation